Policy Network Actors as Units of Public Policy Analysis - Rizky Ilhami (SEAN Institute, 2023)
Developments that have occurred over the last few decades have had an impact on shifting the role of government in shaping public policy, from being the only key actor to becoming one actor among other actors, both government and non-government, who work interdependently through a series of networks. This research aims to explain the emergence and development of the concept of policy network actors as a unit of analysis in the realm of public policy. This research uses a qualitative approach with descriptive methods. The research results show that the formation of a policy network that is responsive to community needs requires strong collaboration between various key actors such as government, the private sector, civil society and international organizations. The importance of openness, transparency and active participation in the policy-making process also stands out as a determining factor in achieving responsive and inclusive policies. In addition, effective monitoring and evaluation mechanisms are key in ensuring that the policies produced remain relevant and can adapt to existing dynamics in society. This conclusion emphasizes the importance of understanding and managing complex dynamics between actors and ensuring that the resulting policies take into account the diverse interests and values in society